Judicial Reluctance and Legal Gaps in Recognizing Gambling as a Ground for Divorce: An Islamic Law Analysis of Decisions of the Pekanbaru Religious Court - Fadel Muhammad; Zulfahmi Bustami; Muhammad Darwis; Pujangga Candrawijayaning Fajri; Naimah Mohamad Nasir (Universitas Muhammadiyah Bandung, 2026)
This study is motivated by the empirical finding that judges in the Religious Court Class 1A Pekanbaru do not explicitly use gambling as a legal ground for divorce, despite its inclusion in Government Regulation No. 9 of 1975 Article 19(a) and the Compilation of Islamic Law (KHI) Article 116(a). Moreover, Law No. 1 of 1974 on Marriage does not specifically recognize gambling as a cause of divorce, resulting in limited legal protection for affected parties. This research aims to analyze judicial reasoning and standards in adjudicating divorce cases involving gambling from an Islamic law perspective. This study employs a qualitative normative legal approach based on secondary data, utilizing statutory, case, and historical approaches. Data were collected through literature review and supported by interviews, and analyzed using qualitative analytical techniques to derive systematic and interpretative conclusions. The findings reveal that judges tend not to explicitly consider gambling as a primary ground for divorce, instead relying on arguments of continuous disputes and conflicts. Consequently, the normative provisions of Government Regulation No. 9 of 1975 Article 19(a) and KHI Article 116(a) are not optimally applied. From an Islamic law perspective, which prioritizes family welfare (maslahah), gambling can constitute a legitimate (syar’i) ground for divorce. In conclusion, there is a normative and practical gap in judicial application, indicating the need for legal reform. This study recommends strengthening legal provisions by explicitly incorporating gambling as a ground for divorce through amendments to Law No. 1 of 1974 to ensure legal certainty and protection.